2019
DOI: 10.1108/jfc-10-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

Transfer pricing, earnings management and tax avoidance of firms in Ghana

Abstract: Purpose This paper aims to investigate how transfer pricing (TP) and earnings management affect tax avoidance of firms in Ghana. Design/methodology/approach The authors use a panel data set from 2008 to 2015 to further shed light on transfer pricing-tax avoidance nexus by examining the complex interaction of three key variables: transfer pricing, earnings management and tax avoidance. Findings The results show that almost all the sample firms have engaged in some form of transfer pricing strategies and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
84
2
38

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(138 citation statements)
references
References 85 publications
14
84
2
38
Order By: Relevance
“…Managers prefer to avoid taxation on personal income and disregard demands from stakeholders (Sofiati & Zulaikha, 2018). Managers also introduce many tax evasion schemes leading to revenue losses (Amidu et al, 2017). Thus, companies prefer to pay extra expenses under the business's supervision (Jensen & Meckling, 1976).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Managers prefer to avoid taxation on personal income and disregard demands from stakeholders (Sofiati & Zulaikha, 2018). Managers also introduce many tax evasion schemes leading to revenue losses (Amidu et al, 2017). Thus, companies prefer to pay extra expenses under the business's supervision (Jensen & Meckling, 1976).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Many multinational companies register transactions with transfer pricing using two different reports, one for management accounting and one for tax reporting (Robu & Căpățină-Verdeș, 2017). Amidu et al (2017) reported that multinationals are expanding their income by maximizing global profits and minimizing global taxes by taking affiliates into low tax rate countries and tax-haven countries. Tax avoidance positively affects business earnings, with many firms carrying out international transfer pricing (Nguyen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research results prove that apart from being used as a resource allocation, transfer pricing is also used as a mechanism to minimize and avoid international taxes [2]. Transfer pricing is used by companies to maximize profits and minimize taxes, because taxes are considered a burden that will reduce profits.…”
Section: B Transfer Pricingmentioning
confidence: 94%
“…Transfer pricing is an economic and legal tool used by business entities for their tax burden optimization.In essence, transfer pricing means intra-company pricing of goods transferred between the enterprise subdivisions located in different countries [7]. Management of the company seeks to increase corporate profits by doing tax avoidance that does not violate applicable tax laws or tax avoidance with accounting methods, such as by moving profits to a country with lower tax rates so that the amount of tax paid becomes lower [4]. To maximize global profits and tax minimization, multinational companies have used several tax avoidance mechanisms as a way to shift taxable income from high tax jurisdictions to low tax jurisdictions to reduce corporate tax obligations.…”
Section: The Influence Of Transfer Pricing On Tax Avoidancementioning
confidence: 99%
“…There was a positive relationship between transfer pricing and tax avoidance. Financial companies more often avoid taxes through manipulation of transfer pricing than non-financial companies [4].…”
Section: Introductionmentioning
confidence: 99%